Caracterização do meio físico e avaliação do desmatamento no município de Cacoal RO de 1986 a 2007, utilizando técnicas de geoprocessamento - Casagrande, Baltazar (2009)
The general objective of this research is conducting the survey and mapping the physical environment and evaluate the deforestation in the municipality of Cacoal, in the state of Rondônia, Brazil, using geoprocessing techniques. This objective was achieved through the elaboration of thematic maps of the studied area, among them, the maps of human use and vegetation cover of the years 1986, 1999, 2005 and 2007. So this research could be accomplished it was necessary the use of modern and relevant materials and efficient computational techniques available, like the planaltimetric letters of Cacoal and Presidente Médice compiled by the Brazilian Institute of Geography and Statistics (IBGE), on the scale of 1:250.000, the geomorphological and soil maps, prepared by RadamBrasil Project, Ministry of Mines and Energy, besides the satellite images of the years 1986, 1999, 2005 and 2007.The obtained results show the elaboration of hypsometric maps, slope of terrain, geology, drainage, sub-basins, road network and soil maps, these mappings could make it easier dimensioning the physical size of the studied municipality. The mapping of human use and natural vegetation covering of the years 1986, 1999, 2005 and 2007 was important for the analysis of deforestation in Cacoal, showing that during the 20 years of colonization, the Indian reservation hasn t changed in its area of forest for agricultural purposes, maintaining 25.60% of the total area of the municipality with native forest. The human use was what grew the most during the colonization of the region, therefore, the area of natural vegetation was the most reduced one because in 1986 42.65% of the area was occupied by natural vegetation and 31.31% by men.In 1999, the natural vegetation area fell to 22.49% and the human use area increased to 51.21%. In 2005, the value of natural vegetation occupied area was about 15.95% and the human use area was about 57.75%, therefore, the natural vegetation decreased about 26.70% of its area, while the human use has increased 26.44%. The area of urban influence also increased in the first 12 years, going from 0.24% to 0.52% and these remained in the 8 following years. With this research it s possible to conclude that the mapping of the physical environment and analysis of the deforestation, the municipality has been deforested since the 1980 s and that if the government fails to take measures to make the local population aware of this fact, soon the areas of natural vegetation will no longer exist in the city, which causes serious environmental impacts. This fact commits not only the physical structure of the municipality, but also the people settled there, because they make their living from the land.